Spring special issue: How do we design a habitat? - Lopes, S. S.; Borges, J. da C.; del Pino Fernandes del Pino, R.; Marat-Mendes, T. (CIDADES, Comunidades e Territórios, 2024)
This Spring Special Issue of CIDADES, Comunidades e Territórios is a continuation of the thematic dossier published in December 2023, where we continue with the goal of offering a space for reflection and discussion, national or international, of housing and habitat, focusing particularly on the “influence and implications of urban design in territorial, social, economic and environmental sustainability”, a long subtitle that aims to express the complex and multifold aspects that need to be contemplated when approaching the habitat notion, as opposed to mere housing-provision.